Biological sulfate reduction rate measurements from different cores of ODP Leg 201 - Kallmeyer, Jens (PANGAEA, 2025)
This dataset provides sulfate reduction rate data, measured with radiotracer incubations. Samples originate from the Peru continental margin from ODP Leg 201 in January-March 2002. Sediment samples were taken with an Advanced Piston Corer (APC), reaching down to 100 meters below sea floor. Samples were incubated on board for 14 to 21 days depending on site and sediment depth at near in-situ temperature (4° - 16°C). After termination of the incubations, the samples were sent back to MPI Bremen for quantification of SRR, using the single-step cold chromium distillation of Kallmeyer et al. (2004, doi:10.4319/lom.2004.2.171)
Keywords: Peru continental margin; sulfate reduction rates; Upwelling